Mental health status of early married girls during the COVID-19 pandemic: A study in the southwestern region of Bangladesh - Nishat, Jannatul Ferdous; Shovo, Taufiq-E-Ahmed; Ahammed, Benojir; Islam, Md. Akhtarul; Rahman, Mohammad Mizanur; Hossain, Md. Tanvir (Frontiers in Psychiatry, 2023)
Background: Due to unemployment, the prolonged lockdown during the COVID-19 pandemic caused panic and deepened poverty, especially among lower-class and marginal people. The related financial crises led to harmful practices such as the early marriage of adolescent girls, which deteriorated these girl’s mental state. Aims: This study attempted to assess the prevalence of mental health problems among early married girls and determine the associated predictors of the growing mental health burden. Methods: This cross-sectional survey was conducted during the third wave of the COVID-19 pandemic in Dumuria Upazila in the Khulna district of Bangladesh. Data were collected purposively from 304 girls who were married off during the COVID-19 pandemic, this was carried out between 22 July and 31 August 2022 by administering a semi-structured interview schedule, with mental health measured by the depression, anxiety, and stress scale 21 (DASS 21). The data were analyzed using IBM SPSS Statistics (version 25), and multiple linear regression was executed in order to predict mental health problems among early married girls. Results: The findings show that the overall prevalence of depression, anxiety, and stress among early married girls during the COVID-19 pandemic in Bangladesh was 60.9% (95% CI: 0.554-0.663), 74.7% (95% CI: 0.698-0.796), and 23.7% (95% CI: 0.189-0.285). The prevalence was relatively higher among girls from the Sanatan (Hindu) religion and younger girls than among Muslim and older girls, respectively. The multiple linear regressions indicate that age, age at marriage, duration of the marriage, spousal occupation, intimate partner violence (IPV), and subjective happiness were the critical predictors of mental health problems among early married girls. Conclusion: Early marriage, along with various adverse outcomes, i.e., IPV, maladjustment, and poor subjective happiness, has resulted in heightened mental health problems for young girls. Policymakers should implement coercive measures to prevent early marriage, especially during social, economic, political, and health crises; in addition, more research is recommended in order to explore the mechanisms that make early married girls psychologically vulnerable and thus formulate protective and preventive programs for addressing such vulnerabilities.